Understanding the psychiatric prodrome of Huntington disease - Rosenblatt, Adam (BMJ Group, 2007)
Presymptomatic and early symptomatic gene carriers show greater prevalence of depression and irritability than controls. Depressive symptoms worsen with proximity to onset